Fire Incident during Coal Cargo Operation: A Case Study in MV Manalagi Tisya - Sujud Romadhoni Alfitra; Moh Zaenal Arifin; Ria Hermina Sari (Dinamika Bahari, 2025)
Coal is a natural resource consisting of fossilized plant deposits that have undergone a process of decay and petrification for millions of years. In the International Maritime Dangerous Good Code (IMDG code) regulations, coal cargo is included in class IV, which provides for flammable solid objects. This study aims to determine the causal factors, impacts, and efforts to overcome coal cargo fires. In preparing the research results, researchers conducted research using descriptive qualitative methods. The research data source was obtained using the triangulation method, which combines observation, and interviews and is supported by study of documentation it is found that the factors causing the coal cargo fire were the poor quality of coal, the flammable nature of coal and the high temperature which caused the coal cargo in the hold to catch fire. The burning coal cargo has an impact on the loading process which is delayed because the process of extinguishing hotspots in the hold takes a long time. Efforts made by the ship's crew to overcome the burning coal cargo are by cooling down and separating the burning coal to avoid the spread of hotspots. Supervision of the coal loading process by checking the temperature must be done correctly to ensure that the cargo is safe. conduct safety meetings before and after the loading process is carried out to provide knowledge to all crew members about coal loading procedures.